2001
DOI: 10.1097/00000542-200109000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Action on Respiratory Neuron Activity of the Isolated Respiratory Network in Newborn Rats

Abstract: Mu- and kappa-opioid receptor agonists caused reduction of final motor outputs by mainly inhibiting medullary inspiratory neuron network. This inhibition of inspiratory neurons seems to be a result of both a presynaptic and postsynaptic inhibition. The central respiratory rhythm as reflected by the preinspiratory neuron burst rate was essentially unaltered by the agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 0 publications
3
103
1
Order By: Relevance
“…RTN/pfRG provides a major excitatory drive to the central respiratory pattern generator (CPG) (Fukuda et al, 1993;Nattie and Li, 2000;Feldman et al, 2003;Onimaru and Homma, 2003), but its functional role within the respiratory network remains unclear. The phasic and often preinspiratory discharge pattern of pfRG neurons in neonate preparations supports a pacemaker neuron-based inspiratory or expiratory rhythmogenic role for pfRG (Onimaru et al, 1995;Takeda et al, 2001;Janczewski et al, 2002;Onimaru and Homma, 2003), whereas the more tonic discharge of adult RTN neurons in vivo favors a central chemoreceptor function Mulkey et al, 2004;Putnam et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…RTN/pfRG provides a major excitatory drive to the central respiratory pattern generator (CPG) (Fukuda et al, 1993;Nattie and Li, 2000;Feldman et al, 2003;Onimaru and Homma, 2003), but its functional role within the respiratory network remains unclear. The phasic and often preinspiratory discharge pattern of pfRG neurons in neonate preparations supports a pacemaker neuron-based inspiratory or expiratory rhythmogenic role for pfRG (Onimaru et al, 1995;Takeda et al, 2001;Janczewski et al, 2002;Onimaru and Homma, 2003), whereas the more tonic discharge of adult RTN neurons in vivo favors a central chemoreceptor function Mulkey et al, 2004;Putnam et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…In essence, we hypothesize that the CPG input to the chemosensitive neurons of RTN/pfRG is a simple feedback. This feedback originates from phasically active respiratory neurons and therefore produces the respiratory modulation of RTN/pfRG previously observed under various experimental conditions (Connelly et al, 1990;Nattie et al, 1993;Onimaru et al, 1995;Bodineau et al, 2000;Takeda et al, 2001;Janczewski et al, 2002;Onimaru and Homma, 2003).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…So, why does the Dscam Ϫ/Ϫ mouse show perinatal death and why does the Dscam ϩ/Ϫ mouse can survive? The opiate surge at neonatal stage would depress the excitability of Insp neurons in the preBötC but not that of Pre-I neurons in the pFRG (Takeda et al, 2001). It is therefore hypothesized that the pFRG is an "anti-apnea" center that promotes breathing immediately after birth (Jacquin et al, 1996).…”
Section: Loss Of Pre-i Synchroneity In Dscammentioning
confidence: 99%
“…The other neuronal group, the pFRG (Onimaru and Homma, 2003;Onimaru et al, 2004), contains neurons that discharge during the preinspiratory phase and that are synaptically connected to neurons of the PBC (Takeda et al, 2001;Janczewski et al, 2002;Mellen et al, 2003). Interestingly, two recent studies from Onimaru and Homma performed in rat showed (1) that neurons exhibiting a preinspiratory discharge could not be found before the developmental stage E19 and (2) using optical recordings in embryonic rat brainstem-spinal cord preparations that the pFRG might not be functional before E19 (Onimaru and Homma, 2005).…”
Section: The Hf Generator Is the Respiratory Generatormentioning
confidence: 99%